2020
DOI: 10.21037/tcr.2020.03.50
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1/3/4 as novel biomarkers for the prognosis of human breast cancer

Abstract: Background Anomalous expression of glucose transporters (GLUTs) has been observed in a variety of tumor tissues. Although GLUT factors have been shown to have prognostic value for some cancer types, detailed bioinformatics investigation of the factors contributing to the prognostic prediction for patients with breast cancer (BC) has not yet been performed. Methods In this study, we examined the transcription levels of GLUT1 , GLU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 67 publications
(58 reference statements)
1
13
1
Order By: Relevance
“…The findings of the present study are in complete agreement with other studies which proved that increased glucose uptake in breast cancer cells was significantly linked to high GLUT4 expression which was associated with poor prognostic parameters and poor survival outcome ( DeBerardinis et al, 2008;Garrido et al, 2015;Zeng et al, 2020). Moreover, Garrido et al (2015) proved that loss of GLUT4 impairs the viability of breast cancer cells via metabolic reprogramming of tumor cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study are in complete agreement with other studies which proved that increased glucose uptake in breast cancer cells was significantly linked to high GLUT4 expression which was associated with poor prognostic parameters and poor survival outcome ( DeBerardinis et al, 2008;Garrido et al, 2015;Zeng et al, 2020). Moreover, Garrido et al (2015) proved that loss of GLUT4 impairs the viability of breast cancer cells via metabolic reprogramming of tumor cells.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Garrido et al (2015) proved that loss of GLUT4 impairs the viability of breast cancer cells via metabolic reprogramming of tumor cells. On the other hand, Zeng et al (2020) showed that downregulation of GLUT4 in breast cancer cells was associated with poor overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of nanoparticles could be mediated by interaction of maltoheptaose corona with cell receptors promoting MH-b-PS@TMC internalization by cells, which could be endocytosis-dependent. It is presumable that the overexpression of the glucose transporter family [50] and in particular of glucose transporter 1, GLUT 1, by the MCF-7 cell line could provide a preferential entry route for maltoheptaose-coated nanoparticles, as previously observed also for glucose-modified PAMAM-based dendrimers loaded with doxorubicin [51]. This could result in selective toxicity of MH-b-PS@TMC against highly proliferating cells, with respect to non-cancerous tissues, further improving their therapeutic index with respect to free TMC.…”
Section: Encapsulation Efficiency Drug Loading and In Vitro Release Kinetics By The Hplc-uv Methodsmentioning
confidence: 99%
“…Hence, elevated transcription of GLUT-3/4 can suggest as a potential prognostic marker (better prognosis) for breast cancer patients. 24 In addition, metaanalysis illustrates the association between GLUT-1 overexpression and poor prognosis in breast cancer, notably these results are more reliable for Asian patients who were mostly included in the studies. 25 As such, GLUT-1 expression is associated with poor prognosis as well as being metabolic biomarker for the Lauren classification in locally advanced gastric cancer.…”
Section: Glycolysismentioning
confidence: 97%